Pilomatrixoma in Head and Neck - Tulachan, B; Parajuli, R (Nepalese Journal of ENT Head and Neck Surgery, 2013)
Nepalese Journal of ENT Head and Neck Surgery, Vol. 3 Issue 1 (Jan-June 2012) Page 11-12 DOI: http://dx.doi.org/10.3126/njenthns.v3i1.8181